Ligand modification to stabilize the cobalt complexes for water oxidation. (14th December 2017) - Liu, Si; Lei, You-Jia; Xin, Zhi-Juan; Xiang, Rui-Juan; Styring, Stenbjörn; Thapper, Anders; Wang, Hong-Yan
Abstract: Ligand modifications with electron-withdrawing and electron-donating groups were applied to afford three novel mononuclear cobalt-based catalysts [Co(TPA-R)] 2+ (TPA = tris(2-pyridylmethyl) amine; R = tri-α F, 1 ; R = tri-αOMe, 2 ; R = mono-αF, 3 ) for water oxidation. Characterization of the catalysts shows that steric and electronic factors play important roles in inhibiting spontaneous intermolecular dimerization of two cobalt centers, and influence the catalytic behavior. Complex1 exhibits the best catalytic ability and stability, showing a good efficiency with TOF of 6.03 ± 0.02 mol (O2 )/(mol (cat)*s) in photo-induced water oxidation experiments using Ru (bpy)3 2+ as photosensitizer and Na2 S2 O8 as electron acceptor. The bulky electron donating groups in2 led to degradation of the complex and formation of CoOx particles acting as the real catalyst. Electron-withdrawing substituents on the TPA ligand can stabilize the catalyst under both electrochemical and photo-induced conditions, with the enhancement increasing with the number of the electron-withdrawing groups. Graphical abstract: Highlights: Three Co catalysts with modified TPA ligands were synthesized for water oxidation. Catalysts exhibited good performance for photo-induced water oxidation. Substituents on TPA ligands affect the catalytic behaviors and stabilities. Stabilities of the catalysts are well characterized by inhibited experiments. Structure activity and stability relationship is expected to establish.